A V-Cycle Multigrid for Quadrilateral Rotated $Q_1$ Element with Numerical Integration (Journal of Computational Mathematics, 2021)
In this paper, a V-cycle multigrid method is presented for quadrilateral rotated $Q_1$ elements with numerical integration.